Multi-Actors in Meeting Fertilizer Needs in Maros Regency - Faisal, Andi Fahri (Journal of Management and Administration Provision, 2024)
This paper examines the management of the subsidized nutsrient support scheme in the Maros Regency in South Sulawesi, in terms of public administration, using the tri-angle theory of strategic government of John Bryson so as to query the schematism of legitimacy, the organizational capacity, and creation of the public value. Using a qualitative descriptive method, we conducted policy report (15 reports) and RDKK document analyses, site observations at five centers of the distribution, and interviews with 20 stakeholders (government officials, legislators, farmers, distributors). The results highlight seven governance issues: inappropriate type of fertilizer, inappropriate brands, little effects on agricultural production, politicization of distribution of fertilizers, inadequate distribution support, poor participation of farmers and incomplete farmer and land information. These limitations indicate poor legitimacy since it is not accompanied by transparent and politically independent procedures, in which farmers have no say in the decision making, something that undermines trust and fairness. Limited source of sufficient technical assistance, unreliability of data system, poor inter-actor coordination are constraints of organizational capacity that lead to inefficient distribution practices. In addition, the program has shown little in the way of public value creation, having little to no impact on increasing crop yields or crop farmer welfare levels and instead creating dependency and not empowerment. The proposed reforms which include the implementation of the farmer-led councils, transparent allocation process, and results-based assessment aim at improving governance of the agricultural subsidies in Maros and other similar contexts in order to achieve food security and empower the farmers.